(3GdHdGZI GdeaJQi YdjgG Hjf GdCUGdI hGdJHYjI (B/s - (3YHGS, aVd MSfs 1932-2011 ((3YeGf (B- (3GdCQOf (B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY ,s, 2019)
(3jMJhj Ydi OQGSI LOjOI aj LdgG, LYdgG GdHGMK aj JegjO hCHhGH KdGKI (B: (3Hjf aj GdJegjO Cef LOjI GdCee dG Jchf EdG HGdeMGaXI Ydi GdJQGK, hJMOK aj GdHGH GdChd HEjLGR Yf GdYQHjI hNUGFUgG GdPGJjI hGdecJSHI, hYf HYV GdbVGjG PGJ GdUdI HgPG GdehVhY, ceG NUU aUdG dTgGOGJ GdYdeGA bOjeG hMOjKG, YQHG hZjQ YQH hJMOK aj GdHGH GdKGfj Yf JGQjN GdHdGZI, hMUjdI aj aUdjf GKfjf (B: (3GdChd (B: (3SdjbI GdYQH GddZhjI, hGdKGfj fTCI GdHdGZI, hGdKGfj fTCI GdHdGZI hJWhQgG(B. (3GdHGH GdKGfj hgh GdZGjI ef GdcJGHGJ aLYdg aj aUhd KdGKI (B: (3JMOK aj GdChd YeG QejJ Hg GddZI GdYQHjI HYGeI, hJMOK aj GdaUd GdKGfj Yf GdTHgGJ GdJj CdbjJ aj GdHdGZI GdYQHjI HNGUI, hef MhdgG, hbO JJHY gPg GdTHgGJ GdJj MGhd CUMGHgG EMGWJgG HgGdGJ eRNQaI, hMGhdhG cPdc Cf jdHShgG ef CKhGH eMceI ZjQ TYHjI aj fSLgG, hMGhdhG Cf jVjahG YdjgG ef GdUHZI GdYdejI, hdcf Pdc cdg de jLO TjFG hNUU GdaUd GdKGdK Yf CFeI GdHdGZI de jCdhG LgOG ajeG cJHhg(B.s
(3HHdjhLQGajI (B: (3UaMI (B305-308.s
Keywords: (3Yde GdHdGZIs; (3GdHdGZI GdYQHjIs